The International Diffusion of Mobile Commerce: A Coupled Hazard Approach - KAUFFMAN, Robert J. (Institutional Knowledge at Singapore Management University, 2005)
The convergence of the Internet, electronic commerce, and wireless technology has created the basis for the rapid global diffusion of mobile commerce. We believe that one approach to understand mobile commerce diffusion is to study the diffusion of digital mobile devices required in mobile commerce activities. Although prior research in technology diffusion has identified a set of variables that affect the entire diffusion process, our knowledge about the factors that dominate at different states of a diffusion process is still incomplete. This research puts forward a new theoretical perspective to enable managers to better understand the states of technology diffusion in the context of digital mobile phones. Our empirical methods involve a coupled-hazard analysis of an interdependent event model to test the effects of country characteristics, the digital and the analog mobile phone industry characteristics, and the regulatory policies on various states of digital mobile phone diffusion across countries. We conduct non-parametric and parametric survival analysis of the model. The results illustrate a broader set of factors that drive the diffusion speed from the early to the partial diffusion state than from the introduction to the early diffusion state.